Neurodynamic properties of attacking players in team sports - Lyzohub , Volodymyr; Nechyporenko , Leonid; Pustovalov , Vitalii; Korol , Tetiana; Khaliavka , Roman; Hrebiniuk , Nataliia (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Scientists indicate that neurodynamic functions, which include innate individual-typological properties of the higher departments of the central nervous system and sensorimotor reactions of varying degrees of complexity, have a direct impact on the success of human activity in many areas of life, including sports. The main function of forward players in sport games is to effectively complete the attacking actions of their own team. An interesting question is whether there can be differences in the manifestations of neurodynamic functions of forward players specializing in different sport games. The goal of the research is to find out the peculiarities of the manifestation of neurodynamic properties of for-ward players specializing in various types of sport games. Materials and Methods. The individual and typological properties of nervous processes and sensorimotor re-actions of various degrees of complexity were determined in forward players of professional sport game teams (volleyball, basketball, football, field hockey and ice hockey) using the ‘Diagnost-1M’ computer system. Research Results. Differences in the indicators of sensorimotor reactions of various degrees of complexity and individual typological properties of higher nervous activity were established analyzing the results of the manifestation of neurodynamic functions in forward players, representatives of various sport games. Forward basketball and volleyball players were characterized by the best indicators. Significant differences (p<0.05) were established according to the study results on the manifestation of neurodynamic functions among sportsmen, representatives of various sport games. Conclusions. Data on the peculiarities of the manifestation of neurodynamic properties of forward players, representatives of various sports may indicate a dependence on the specifics of competitive activity inherent in various types of sport games.